Left-over luggages neatly stacked in the corridor - Mumbai Archive Project (Jio Institute, 2024)
Kudds allows storage for left-over luggage at no extra cost. The trunks are neatly stacked on top of each other along the wall, saving floor space. With dwindling occupancy, nowadays more trunks vie for space in the corridors than actual guests staying there.